Branching analysis of β-cyclodextrin-based poly(N-isopropylacrylamide) star polymers using triple detection SEC - Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
For the first time, poly(N-isopropylacrylamide) (PNIPAAm) star polymers with a β-cyclodextrin core are characterized in detail by size-exclusion chromatography (SEC) with triple detection to experimentally verify the number of arms. A combination of a refractive index detector, multi-angle laser light scattering detector, and an online-viscosimeter was used for branching analysis. At first, the SEC system was calibrated and the detector setup was validated using linear polystyrene reference polymers. The applicability of the established triple detection SEC for branching analysis was shown by the analysis of two commercially available polystyrene star polymers. Due to the high molar masses of the star polymers, both the contraction ratio g and g′ could be determined independently, thus allowing the calculation of the viscosity shielding ratio ε. Finally, the branching analysis of the PNIPAAm star polymers could experimentally confirm the assumed arm number of up to 21 arms. Moreover, an increasingly compact molecular structure and the influence of the arm number on the viscosity shielding ratio could be shown.
Keywords: Size-exclusion chromatography; triple detection; branching analysis; star polymers; poly(N-isopropylacrylamide); β-cyclodextrin

End Group Stability of Atom Transfer Radical Polymerization (ATRP)-Synthesized Poly(N-isopropylacrylamide): Perspectives for Diblock Copolymer Synthesis - Herberg, Artjom; Yu, Xiaoqian; Kuckling, Dirk (Polymers)
Keywords: controlled radical polymerization; atom transfer radical polymerization; end group determination; N-isopropylacrylamide; block copolymerization; smart polymers; temperature sensitive polymers; lower critical solution temperature; ESI-TOF mass spectrometry; ion mobility separation; size exclusion chromatography

Thermoresponsive Catechol Based-Polyelectrolyte Complex Coatings for Controlled Release of Bortezomib - Reis, Berthold; Vehlow, David; Rust, Tarik; Kuckling, Dirk; Müller, Martin (International Journal of Molecular Science)
Keywords: catechol chemistry; poly(caffeic acid); polyelectrolyte complex coatings; thermoresponsive coatings; controlled release; bortezomib; multiple myeloma

Oxygen sensing by fluorescence quenching of [Cu(btmgp)I] - Herres-Pawlis, Sonja; Berth, Gerhard; Wiedemeier, Volker; Schmidt, Ludger; Zrenner, Artur; Warnecke, Hans-Joachim (Journal of Luminescence)
A fluorescence study of acetonitrile solutions of bis(tetramethylguanidine)propane, copper(I)-iodide and [Cu(btmgp)I] was performed and the chemical reaction of the latter species with O2 was investigated at room temperature. The actual quenching process via O2 gassing was studied and an exponential dependence of the fluorescence intensity with respect to the complex concentration was observed. Furthermore the survey was deepened on time resolved fluorescence properties of solved [Cu(btmgp)I] in a wider concentration range. The applicability of this complex for O2 sensing inside a microreactor system was proven by confocal fluorescence measurements. It was shown that the investigated system can be used for oxygen sensing in the copper concentration range from 10−2 to 10−9 mol/l.
Keywords: Copper Oxygen Fluorescence quenching N donor ligands